Construction of the Use of Social Media in Coastal Communities, Belawan District, Medan City - zulkifli zulkifli; muzayanah muzayanah; muya syaroh iwanda (Universitas Dharmawangsa Medan, 2026)
Digital technology, especially social media, can now be considered a platform for people to exchange ideas, information, lifestyles, socialize, and other things. In addition, it has brought significant changes to various aspects of people's lives, including in coastal areas. Social media not only functions as a means of communication but also as an important platform for various social, economic, and cultural activities. The Belawan District, which is a coastal area in the city of Medan, has a unique community, with the majority of its population depending on the fisheries, trade, and small and medium-sized businesses for their livelihoods. In coastal communities, social media has been utilized as a tool for interaction and information to promote businesses. Fishermen, dealers, and local groups have begun to adapt social media as a strategy to expand their networks and increase their income. However, this will be difficult to implement. Even though the use of social media is increasing, there are still various challenges, such as limited internet access, low digital literacy, and the potential for negative impacts, such as the spread of hoaxes and uneducational content, which can lead to the decline of children in coastal areas. The urgency of this research lies in the need to understand how social media can be effectively utilized in the lives of coastal communities to overcome the various problems they face. This study aims to examine how social media is used among coastal communities in Belawan District, including the factors that influence its use, the impacts it has, and the opportunities that can be exploited to improve their welfare. The research method used to solve this problem is qualitative research.